Penafsiran Imad Zaki al-Barudi tentang Berjilbab bagi Perempuan dalam Islam (Analisa terhadap Ayat-ayat tentang Berjilbab dalam Tafsir Al-Qur’an Wanita Karya Imad Zaki Al-Barudi) - Nina Inayatul Maula (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
The phenomenon of the use of the hijab today has experienced a shift in meaning, the hijab is no longer a cover for the aurat because it has become a trend or fashion for Muslim women today so that many are not in accordance with the rules of Islamic law as it should be. This study aims to discuss her interpretation of the hijab in modern times in Tafsir Al-Qur'an Wanita. The method used in this research is the maudhu'i method, which is to study the Qur'anic description of a problem in order to reveal the intent contained or hidden in the Qur'an, in order to obtain clear and comprehensive results. The result of this research shows that the interpretation of verses about hijab according to Imad Zaki al-Barudi there are several factors behind the trend of hijab, including; social, culture, popularity, fashion, development of the times and technology so that new things appear that can change the nature of the hijab which is not in accordance with Islamic law. Then he also mentioned some rules in wearing the hijab in accordance with Islamic law that has been explained in this study. The conclusion of this study shows that the command in the verse of hijab is addressed to women who feel uncomfortable with the disturbance of men when they have to show the beauty and sexuality of their bodies so that it can move men's hearts. In fact, they feel very uncomfortable and feel very disturbed.